A multi-agent approach for enhancing transient stability of smart grids. (May 2015) - Rahman, M.S.; Mahmud, M.A.; Pota, H.R.; Hossain, M.J.
Highlights: A multi-agent based protection framework is proposed to enhance the stability of smart grids. Direct and time-domain simulation methods are used to calculate critical clearing time. Intelligent agents communicate with each other to ensure on-line capability and scalability. Proposed scheme dynamically adapts the changes in loads of generators. Abstract: Transient stability, an important issue to avoid the loss of synchronous operation in power systems, can be achieved through proper coordination and operation of protective devices within the critical clearing time (CCT). In view of this, the development of an intelligent decision support system is useful for providing better protection relay coordination. This paper presents an intelligent distributed agent-based scheme to enhance the transient stability of smart grids in light of CCT where a multi-agent framework (MAF) is developed and the agents are represented in such a way that they are equipped with protection relays (PRs). In addition to this, an algorithm is developed which assists the agents to make autonomous decision for controlling circuit breakers (CBs) independently. The proposed agents are responsible for the coordination of protection devices which is done through the precise detection and isolation of faults within the CCT. The agents also perform the duty of reclosing CBs after the clearance of faults. The performance of the proposed approach is demonstrated on a standard IEEE 39-bus test system by considering short-circuit faults at different locations under various load conditions. To further validate the suitability of the proposed scheme a benchmark 16-machine 68-bus power system is also considered. Simulation results show that MAF exhibits full flexibility to adapt the changes in system configurations and increase the stability margin for both test systems.